Textural and geochemical characteristics of the Ajali sandstone, Anambra basin, Se Nigeria: implication for its provenance (2010)
"This study presents the mineralogical, textural and geochemical characteristics of the regional Maastrichtian Ajali Sandstone in Anambra Basin, SE Nigeria. The intent is to highlight possible constraints on the chemical weathering conditions of the source materials on one hand, and to infer the provenance on the other hand. The investigation approach involved field studies and collection of samples from 12 different outcrop locations, followed by laboratory studies involving grain-size analysis (GSA), major and trace elements analyses using the X-ray fluorescence (XRF) method as well as thin section petrography. Field studies show that the sandstones are friable at all locations and range in color from white in freshly cut stone, to reddish brown on weathering. In addition, the sandstone units are cross-bedded and show graded bedding exemplified by fining upward sequence. Textural examination indicates that the sandstones range from fine to medium sands, constituting about 76 to 99% sand fraction, with graphic mean grain size of 0.23 to 0.53 mm. Standard deviation (sorting) ranges from 0.56 to 1.24 Ø and implies moderately well sorted sediments. Inferred from the textural indices, the depo-environmental discrimination of the Ajali Sandstone revealed a fluvial/river system-dominated sedimentary process. The sandstones are quartz arenite with quartz greater than 90% and less than 5% K-feldspar which indicate a predominant basement source as also revealed by the heavy mineral assemblages. In addition, major elemental oxides shows SiO2 content greater than 96% for the fresh Ajali Sandstone samples with extreme depletion of mobile oxides such as Na2O, CaO and the ferromagnesian minerals through weathering and sedimentary processes. Provenance and tectonic setting discrimination using geochemical data and compositional maturity revealed typical felsic igneous-dominated cratonic environment while inter-elemental ratios (such as Zr/Cr, Y/Ni, Th/Sc, La/Sc and La/Co) and ternary plots (e.g. Th–Sc–Zr; La- Th–Sc and Th-Co-Zr) reflect passive continental margin setting for the Ajali Sandstone. Consequently, the source area is constrained to the Precambrian basement rock units of Adamawa-Oban massif areas to the east of the Anambra Basin and the adjacent Abakaliki Anticlinorium. "